Application of palliative care in demented patients: the caregivers’ point of view - Zapponi, Sabina; Ferreira, Aline; Galvagni, Paolo; Roccatagliata, Camilla; Rodolfi, Simone; Spina, Miriana; Foà, Chiara; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2018)
Background: The 38/2010 law has widened the supply of palliative care for patients with chronic and degenerative illness. Dementia is a chronic and debilitating illness and it requires specific, complex and constant assistance, involving the health professionals’ community and family, and should also benefit from palliative care. But what do the caregivers of these patients think about it? Aim: To explore the point of view of caregivers accompanying dementia patients regarding palliative care and the accompaniment of the medical team. Method: A qualitative method with phenomenological approach: 29 semi-structured interviews have been submitted to caregivers of patients suffering from dementia. The interviews were submitted to analysis of thematic content. Result: In the majority of cases the caregiver is a member of the family and holds this position because of the affective relationship he/she shares with the patient. They too live the illness of the relative as if it were theirs. The caregiver doesn’t know about palliative care or has only heard of it, but is resistant to the application of this care, especially when its correct meaning and use are explained. At the same time, the health professionals’’ role is important when it comes to taking decisions: caregivers rely completely on the team’s competence and on their judgement. Conclusion: A correct sharing of knowledge is fundamental. The healthcare professionals must be trained in palliative care in order to correctly inform caregivers and to avoid false beliefs about or resistance to the application of these useful pathways.